The Effect of Service Quality and Product Quality on Customer Satisfaction and Its Impact on Participant Loyalty in BPJS Ketenagakerjaan - Parlianita Parlianita (Priviet Social Sciences Journal, 2022)
Implementation of the Social Security program is based on the Labor Law but BPJS Ketenagakerjaan continued to have a competitor that is national or foreign private insurance. In order to continue to grow and be able to protect all workers then BPJS Ketenagakerjaan must compensate and make various efforts and strategies include improving service quality, improve product quality so that the satisfaction of the participants remain loyal and choose BPJS Ketenagakerjaan as a solution to the transfer of risk faced by employers and workers. Formulation of the problem in this research is the extent to which the influence of Service Quality and Product Quality on Customer Satisfaction and Loyalty Impacts for Participants in BPJS Ketenagakerjaan. The aim of this study was to determine and analyze the influence of Service Quality and Product Quality and its Impact on Satisfaction to Loyalty Participants BPJS Ketenagakerjaan. The theory used is the theory that analyzes the dimensions of service quality services, and the factors that affect the quality of service or service as well as the theory of product quality and product dimensions, the theory of customer satisfaction that measures customer satisfaction and factors that influence satisfaction according to Kotler. This research approach is supported by a case study with a survey. This type of research is deskreptif and quantitative research, the nature of research just to get a picture of a situation and problems and interpret. The population in this study were 12.5 million workers, with a sample size of 100 respondents. Data were collected through questionnaires and documentation study . Hypothesis testing using multiple linear regression analysis, F test and t test to determine the effect of independent variables on the dependent variable on rate of 95 % ( α = 0.05). The results showed that the quality of service and product quality directly affect customer satisfaction and an impact on customer loyalty . The most dominant variable affecting satisfaction is the quality of service that is equal to 50.2 % and variable product quality that is equal to 32.2 % . The variable quality of the products also directly affects customer loyalty significant value amounted to 22.4 % , while the variable quality of service does not affect the loyalty due to the significant value of only 5.3% . The coefficient of determination ( R ² ) showed independent variables studied were able to explain 48.5 % overall at loyalty variable , while the remaining 51.5 % is explained by other independent variables that are not included in this study .